THE INFLUENCE OF FINTECH PAYMENT, ACCOUNTING KNOWLEDGE, AND FINANCIAL SELF-EFFICACY ON FINANCIAL MANAGEMENT BEHAVIOR - Muhammad Barik Rizqi; Luke Suciyati Amna (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study examines the influence of Financial Technology Payment, Accounting knowledge, and Financial self-efficacy on the financial management behavior of students of the Accounting Study Program at the University of Bandar Lampung. This study took a sample of 97 people who were selected by purposive sampling, data was collected through the distribution of questionnaires and data analysis methods were carried out with multiple linear regression tests assisted by SPSS version 27 application. The results of the study show that the three independent variables contribute positively and significantly to students' habits in managing their finances. Fintech Payment facilitates the transaction process and financial recording, accounting knowledge improves understanding of financial management concepts, and Financial self-efficacy encourages confidence in financial decision-making. Simultaneously, these findings highlight the importance of integrating financial technology, accounting knowledge, and self-confidence development to improve students' ability to manage personal finances.